Dolomite dust filled glass fiber reinforced epoxy composite: Influence of fabrication techniques on physicomechanical and erosion wear properties. Issue 1 (16th November 2021) - Verma, Shashi Kant; Gangil, Brijesh; Gupta, Ashutosh; Rajput, Nitesh Singh; Singh, Tej
Abstract: This article investigates the effect of fabrication techniques on the physical, mechanical, and erosion wear properties of glass fiber reinforced dolomite dust‐filled epoxy composites. The composites were fabricated by hand layup and vacuum‐assisted resin transfer molding (VRTM) techniques with fixed glass fiber (20 wt%) and varying dolomite dust (0 to 15 wt%) with epoxy resin. In physical properties, the experimental density consistently increased with the increase in the dolomite hand layup and the VRTM process; in opposite the voids content increased in the hand layup process and decreased in the VRTM process. In mechanical properties, the hardness, impact energy, and interlaminar shear strength increases while tensile and flexural strength consistently decreases with dolomite dust content. Using Taguchi's optimization technique, the erosion wear of the fabricated composites was also evaluated at different impingement angles, impact velocities, and erodent sizes. Erosion test results indicate that the VRTM process fabricated composite has minimum erosion wear compared to the hand layup process. The eroded surfaces were studied using a scanning electron microscope to understand the erosion behavior of particulate‐filled fiber reinforced polymer composites. Abstract :